The nematophagous fungus Verticillium chlamydosporium: aspects of pathogenicity - Segers, Rudi (1996)
Verticillium chlamydosporium is a fungal pathogen of eggs and females of plantparasitic nematodes. The fungus produced an alkaline serine protease in submerged culture. This enzyme, VCPI, was characterized as a class II subtilisin, based on amino acid sequenceh omology. Several of its characteristics, e.g. molecular mass (33 kDa), pI (ca 10) and broad substrate utilisation, are typical of fungal subtilisins. Although some immunological cross-reactivity existed with other enzymes of this class, an antigenic fingerprint was obtained that was distinct, even from the subtilisin that was its closest homologue based on amino acid sequence, PrI from the entomogenous fungus Metarhizium anisopliae.